Science Teachers’ Understanding on Science Literacy and Integrated Science Learning: Lesson from Teachers Training (Program Studi Pendidikan IPA Fakultas Matematika dan Ilmu Pengetahuan Alam (FMIPA), 2018)
One of the weaknesses of secondary science teachers today is the lack of ability to develop integrated science learning. Descriptive study, followed by developmental research has been done to determine the factors that caused the weakness, to find the right solution. In addition, the research that involving 25 teachers as subject, has also examined how far the treatment can be able to overcome the problems. The descriptive research shows that almost all of teachers did not have skillful on how to teach science in integrated way. This is because all of teacher's background is not from fully integrated science education. Most of them came from biology, physics and chemistry education. They have actually attended the training (arranged by government) on integrated science teaching, but it apparently have not succeeded. The eight steps of learning approach has been developed and implemented along the training: (1) Building common perception on science literacy, (2) integrated science analysis based on current curriculum and lesson analysis, (3) presentation, (4) designing lesson plan in groups, (5) simulation, (6) designing lesson plan individually, (7) evaluation-reflection, and (8) rewards. After the treatment, the teacher's ability to develop the lesson plans eventually improves much better as well as the understanding on integrated science concepts. Only three teachers have to follow remediation in making lesson plan because they still not fulfill requirement of graduation (minimum 80% achievement of conceptual understand, performance, and lesson plan product).